The Female Character in Chinese Animated Films: Gender and Negotiating Identity in the Context of Reform and Opening-up of the Chinese Economy - Yinghong, Deng; Phanlukthao, Peera (Journal of Ecohumanism, 2025)
This qualitative research examines female characters in Chinese animated films to explore gender and identity negotiation within the context of China’s economic reform. The study focuses on: (1) the social and cultural history of Chinese women and animated films, emphasizing the interplay between women and female characters; (2) gender perspectives in Chinese animated films during economic reform; (3) the negotiation of identity through female representation; and (4) analyzing the "Fox Woman" character as a unit of analysis. The findings reveal that prior to economic reform, gender concepts in China were deeply rooted in traditional feudal ideologies, including male dominance, restrictive family and marriage systems, and unequal access to education. However, reform and opening up introduced foreign cultural influences and evolving audience aesthetics, fostering negotiations among the state, creators, and audiences about identity and gender representation. The government encouraged creators to align female characters with contemporary values, while audiences progressively internalized these gendered transformations, reshaping social and moral values. Key insights include: (1) Female characters in Chinese animated films act as mediators of new social relationships among the state, creators, and audiences, fostering multi-layered social interactions. (2) These characters serve as cultural ambassadors, breaking away from traditional stereotypes to portray independent and complex female identities. (3) Gender representation in animation has evolved, reflecting a shift from male-dominated norms to diverse and modern portrayals of women. (4) Female consciousness in animated characters mirrors broader societal changes, moving from subjugation to empowerment. (5) The intersection of traditional culture with modern aesthetics offers innovative frameworks for female character development. This research highlights the evolving gender culture in contemporary Chinese society and the transformative role of media, offering theoretical and practical insights into gender analysis and identity negotiation.